Rare Naegleria fowleri meningoencephalitis diagnosed via combined molecular biology and metagenomic sequencing techniques: a case report - Yuanjing Kou; Jiayao Zhang; Dan Wang; Lidan Cui; Qi Sun; Yanqi Lv; Ying Liu; Zhiquan He; Yuling Zhao; Hongwei Zhang; Jun Su; Yaobao Liu; et al. (Infectious Diseases of Poverty)
Abstract Background Naegleria fowleri, a pathogenic free-living amoeba, causes primary amoebic meningoencephalitis (PAM), a rare but devastating disease with acute onset, rapid progression, and > 95% mortality. Despite its rarity, the catastrophic outcomes associated with this infection underscore the critical importance of prevention. In this report, we present a rare pediatric fatality caused by PAM in China, highlighting the challenges of diagnosis and treatment. Case presentation A 6-year-old child from Lushan County, Henan Province, developed persistent high fever, headache, vomiting, and altered mental status on December 5, 2024. After receiving ineffective local treatment, the child was transferred to the Eastern District of Henan Children’s Hospital on December 7 for further evaluation and management. Upon admission, cerebrospinal fluid was collected for laboratory analysis, and antimicrobial therapy, including amphotericin B, fluconazole, and rifampicin, was promptly initiated. Despite these interventions, the patient’s condition deteriorated rapidly, and the child succumbed to the infection on December 9. Conclusions Clinical and laboratory findings strongly suggest that the child was infected with N. fowleri, resulting in PAM. Epidemiological investigation suggests possible exposure at a public bathhouse. Given the survival characteristics of the N. fowleri and potential habitat expansion due to global warming, this sporadic case underscores PAM's lethal potential. With mortality exceeding 95%, early recognition and prompt intervention are crucial. Clinicians should maintain high suspicion for PAM in patients with compatible symptoms, especially in regions with warm freshwater exposure.